Research on dynamic traffic control strategy of IoT cloud service - Qineng LING; Yichuan WANG; Jiabing YANG; Kan ZHENG (物联网学报)
Flow control is very important to ensure quality of service in cloud service system.A dynamic two-level flow control strategy was proposed.Using the improved minimum connection number algorithm based on the actual cloud service system,the integrated load of the service node was calculated,load balancing was performed on each service node and the load was distributed reasonably.Within the service node,a dynamic hierarchical threshold adjustment strategy was proposed to control traffic dynamically.The actual cloud service system performance test shows that with the dynamic two-level flow control strategy,the RPS of the service node is significantly better than the RPS without the strategy,and the resource utilization of the service node is improved.